Lead(II) Formate in Rembrandt's Night Watch: Detection and Distribution from the Macro‐ to the Micro‐scale. (25th January 2023) - Gonzalez, Victor; Fazlic, Ida; Cotte, Marine; Vanmeert, Frederik; Gestels, Arthur; De Meyer, Steven; Broers, Fréderique; Hermans, Joen; van Loon, Annelies; Janssens, Koen; Noble, Petria; Keune, Katrien
Abstract: The Night Watch, painted in 1642 and on view in the Rijksmuseum in Amsterdam, is considered Rembrandt's most famous work. X‐ray powder diffraction (XRPD) mapping at multiple length scales revealed the unusual presence of lead(II) formate, Pb(HCOO)2, in several areas of the painting. Until now, this compound was never reported in historical oil paints. In order to get insights into this phenomenon, one possible chemical pathway was explored thanks to the preparation and micro‐analysis of model oil paint media prepared by heating linseed oil and lead(II) oxide (PbO) drier as described in 17 th century recipes. Synchrotron radiation based micro‐XRPD (SR‐μ‐XRPD) and infrared microscopy were combined to identify and map at the micro‐scale various neo‐formed lead‐based compounds in these model samples. Both lead(II) formate and lead(II) formate hydroxide Pb(HCOO)(OH) were detected and mapped, providing new clues regarding the reactivity of lead driers in oil matrices in historical paintings. Abstract : X‐ray powder diffraction mapping at multiple length scales revealed the unusual presence of lead(II) formate, Pb(HCOO)2, in several areas of The Night Watch, Rembrandt's most famous painting. A possible chemical pathway resulting in the formation of this compound in historical oil paint was explored via micro‐analysis, notably using synchrotron radiation. New clues on the reactivity of metallic driers in oil systems were thus gathered.